Disturbances of the thermosphere-ionosphere-plasmasphere system and auroral electrojet at 30°E longitude during the St. Patrick's Day geomagnetic storm on 17–23 March 2015. (November 2018) - Klimenko, M.V.; Klimenko, V.V.; Despirak, I.V.; Zakharenkova, I.E.; Kozelov, B.V.; Cherniakov, S.M.; Andreeva, E.S.; Tereshchenko, E.D.; Vesnin, A.M.; Korenkova, N.A.; Gomonov, A.D.; Vasiliev, E.B.; et al.
Abstract: This study presents an analysis of geomagnetic disturbances and ionospheric electron density distribution during the 2015 St. Patrick's Day geomagnetic storm. To study those we have used the satellite-borne and ground-based observations. The St. Patrick's geomagnetic storm covers the interval of 15–23 March 2015, when solar eruptive phenomena (a long-enduring C9-class solar flare and associated CME's on 15 March) and a strong geomagnetic storm on 16–18 March (Dst dropped as strong as –228 nT) were reported. This geomagnetic storm is still the strongest one observed in the current solar cycle. The severe geomagnetic storm on 17-18 March 2015 led to complex effects on the ionosphere. We consider major features of the positive and negative ionospheric storms development at European mid- and high-latitudes. One of the interesting phenomena was observation of the positive ionospheric disturbances during the recovery phase. Using the Global Self-consistent Model of the Thermosphere, Ionosphere and Protonosphere (GSM TIP) we examined the main physical processes that played a major role in dramatic changes of the total electron content and the F 2 layer peak electron density during this storm event. Highlights: All types of the ionospheric disturbances are very well reproduced by GSM TIP model for the 2015 St. Patrick's Day storm. The prompt penetration electric field dominates in producing of the positive ionospheric storm only at the storm beginning, and equatorward neutral wind dominates during several hours after that. We conclude that the neutral composition changes play the most important role in the daytime electron density increase at different latitudes during the recovery storm phase.